(untitled) (Raparin Journal of Humanities (RJH), 2024)
In Kurdish, legal translation as a non-literary translation has received little attention in the field of translation studies. One genre of legal translation that is specifically under-studied is business contracts. This paper analyses and compares features of English and Kurdish business contracts from lexical and syntactic perspectives. It also addresses the issue of LSP lexical and syntactic precision used in the translated Kurdish contracts by translators. To this end, the paper attempts to identify the translation procedures and norms that manifest in translating business contracts from Kurdish into English. As a result, it scrutinizes a set of 20 Kurdish-English business contracts translated by professional licensed translators using Toury’s (2012) three-phase methodology. The translation direction is from Kurdish into English because it is the most practised direction by the translation service providers in Iraqi Kurdistan. The study demonstrates that both Kurdish and English legal languages use similar syntactic and lexical tools in drafting business contracts. It also reveals that initial norms, preliminary norms, and the law of interference are shown in the Kurdish- English translations. It further discloses that transposition, amplification, and couplets are prominently employed to deal with translation challenges. This paper is significant because it is the first attempt to scientifically investigate semantic features of originally written as well as translated Kurdish business contracts. For further research, it recommends a further focus on differences in legal systems and languages between Kurdish and English